Peer victimization during adolescence: concurrent and prospective impact on symptoms of depression and anxiety - Stapinski, Lexine A.; Araya, Ricardo; Heron, Jon; Montgomery, Alan A.; Stallard, Paul (Taylor & Francis, 2014)
BACKGROUND: Peer victimization is ubiquitous across schools and cultures, and has the potential for long-lasting effects on the well-being of victims. To date, research has focused on the consequences of peer victimization during childhood but neglected adolescence. Peer relationships and approval become increasingly important during adolescence; thus, peer victimization at this age may have a damaging psychological impact.